Thoraco-abdominal aortic aneurysm.: Surgical treatment - Danza, Rómulo; Navarro, Teodoro; Baldizán, Jorge; Sáez, Hugo; Domínguez, Juan (Cirugía del Uruguay, 1985)
A case of !horaco-abdominal aortic aneurysm in a 38 years old patient is reported. lts origin probably related to a syphilitic aortitis. lts extention along the spinal cord was from D 1 o to L 2 and transversal dlameter was 10 cm. lts inferior neck was immedlatly over the renal arteries.